FAKTOR FAKTOR YANG MEMPENGARUHI TERJADINYA INFERTILITAS PADA PASANGAN SUAMI ISTRI DI DESA DUWANGAN KECAMATAN DUNGALIYO KABUPATEN GORONTALO - Harismayanti Harismayanti (-, 2021)
The purpose of this research was to determine the factors influence of infertility towards spouse couple in Duwanga village Dungaliyo sub District of Gorontalo District. Design of research was used quantitative methods. The result showed that couples experiencing infertility as a disease (66,7%), who are under stress (76,7%), the genetic effect on infertility as many (63,3%), infertility with abnormal body weight (61,7%), and the environment are exposed (78,3%). It can be concluded that there was factors of disease, sress, genetics, weight, and the environment against infertility toward spouse couples in Duwanga village Dungaliyo District of Gorontalo district.